Expressions of Interleukin-4 and Interleukin-5 in Nodular Prurigo and Pruritic Papular Lesions - Sayekti, Ayu Wikan; Putri, Ann Kautsaria; Winarni, Dwi Retno Adi; Pudjiati, Satiti Retno (Folia Medica Indonesiana, 2024)
Highlights: 1. An examination of IL-4 and IL-5 expressions in nodular prurigo and pruritic papular eruption is crucial for enhancing the effectiveness of biological agent therapy, specifically for HIV/AIDS patients. 2. The findings offer evidence suggesting the possibility of IL-4 as a treatment target for individuals diagnosed with nodular prurigo, as well as IL-4 and IL-5 for those diagnosed with pruritic papular eruption. Abstract Pruritic papular eruption is a dermatosis characterized by pruritic symptoms in patients with human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS). Similarly, nodular prurigo is an itchy dermatosis with lesions and histopathological features that resemble those of pruritic papular eruption. Both conditions share a common etiopathogenesis, which involves the cytokines produced by T helper 2 (Th2) cells. Nodular prurigo and pruritic papular eruption are chronic and frequently recalcitrant, thus posing challenges in treatment. The use of biological agents represents a treatment development for chronic and recalcitrant dermatoses. This study aimed to determine the difference in the mean percentage of interleukin-4 (IL-4) and interleukin-5 (IL-5) expressions between nodular prurigo and pruritic papular eruption lesions, which may establish a basis for further biological agent therapy. A cross-sectional study was conducted using paraffin block preparations of the skin lesions of patients diagnosed with nodular prurigo (n=16) and pruritic papular eruption (n=16). Each paraffin block preparation involved immunohistochemical staining using IL-4 and IL-5 monoclonal antibodies. The expressions of IL-4 and IL-5 were assessed through ImageJ for Windows, version 1.53 (National Institutes of Health and the Laboratory for Optical and Computational Instrumentation, University of Wisconsin, USA) by pathologists. The data were analyzed using an unpaired t-test with a significance level of p<0.05. The analytical results indicated that data on the average age of the two groups, disease duration, and storage sample duration followed a normal distribution (p>0.05). The mean percentage of IL-4 expression was significantly different between the nodular prurigo and pruritic papular eruption groups (p=0.000). However, the mean percentage of IL-5 expression was not significantly different between the two groups (p=0.060). In conclusion, the expression of IL-4 was higher in the nodular prurigo group in comparison to the pruritic papular eruption group. Nonetheless, the expression of IL-5 was comparably high in both the nodular prurigo and pruritic papular eruption groups.